Does Chitala Lopis Really Extinct? An Overview And DNA Barcode (COI) Comparison - Syafruddin Ilyas (International Journal of Ecophysiology, 2022)
The Asian Featherback Fish Or Ikan Belida Is One Of The Most Important Species Of Fish In Indonesia That Is Utilised By Locals As A Food Ingredient. Unfortunately, One Of The Species (Chitala Lopis) Has Already Been Reported Extinct By The IUCN. Nevertheless, Many Publications After That Still Claimed That Chitala Lopis Is Extant. We Study 28 COI Partial Sequences Of Chitala Lopis From NCBI. The Result Showed That Most Of These Sequences Were Not The Actual Chitala Lopis. It Is Probably Either Chitala Hypselonotus Or Chitala Borneensis. This Prediction Is Based On The Unmatch Between The Distribution Of Chitala Lopis COI Sample Origin And The Actual Habitat Of Chitala Lopis, Which Is Endemic To Java Island. However, There Is Also An Article That Reports If Chitala Lopis Is Tried To Be Cultivated. The Misinterpretation Is Perhaps Because Chitala Spp. Is A Complex Species, Which Has Very Similar Morphology. More Study On Molecular Chitala Sp. In Indonesia Is Still Needed To Complete The Unclear Status Of Extinct Chitala Lopis